Reclassification of Hypertensive Outpatients According to New US Guidelines on High Blood Pressure. (5th September 2018) - Tocci, Giuliano; Presta, Vivianne; Figliuzzi, Ilaria; Miceli, Francesca; Citoni, Barbara; Coluccia, Roberta; Paini, Anna; Salvetti, Massimo; Ferrucci, Andrea; Muiesan, Maria Lorenza; Volpe, Massimo
Abstract: BACKGROUND: US guidelines on high blood pressure (BP) have recently proposed a new BP stratification. OBJECTIVE: To evaluate the redistribution of adult outpatients according to 2003 and 2017 US hypertension guidelines. METHODS: We extracted data referred to individuals aged between 40 and 70 years with valid BP assessment from a national, cross-sectional database. The following systolic/diastolic BP strata were considered: (i) 2003 guidelines: 0 = normal (<120/180 mm Hg), 1 = prehypertension (≥120 and ≤139/≥80 and ≤89 mm Hg), 2 = stage 1 (≥140 and ≤159/≥90 and ≤99 mm Hg), 3 = stage 2 (≥160/≥100 mm Hg) and (ii) 2017 American College of Cardiology/American Heart Association guidelines: 0 = normal (<120/80 mm Hg), 1 = elevated (≥120 and ≤129/<80 mm Hg); 2 = stage 1 (≥130 and ≤139/≥80 and ≤89 mm Hg), 3 = stage 2 (≥140/≥90 mm Hg). Cardiovascular (CV) risk profile characterization was based on Framingham, 10-year risk of a first atherosclerotic cardiovascular disease and European score equations. RESULTS: From an overall population sample of 10, 012 individuals, we selected 8, 911 (89.0%) with valid clinic BP data (44.4% female, age = 60.7 ± 6.6 years, body mass index = 28.2 ± 4.9 kg/m 2, clinic BP = 136.8 ± 14.5/82.1 ± 8.3 mm Hg), among whom 339 (3.8%) were in the normal BP range. According to 2003 guidelines, 3, 919 (44.0%) patients had prehypertension, 3, 698 (41.5%) had stage-1 and 955 (10.7%) had stage-2 hypertension. According to 2017 guidelines, 635 (3.8%) patients had elevated BP, 3, 284 (36.9%) had stage-1 and 4, 653 (52.2%) had stage-2 hypertension. New BP classification moved 37% individuals from "pre-hypertension" to "stage 1" and 41% from "stage 1" to "stage 2" hypertension, respectively. CONCLUSIONS: Redistribution of hypertensive patients according to 2017 US hypertension guidelines compared with previous ones may help to better identify uncontrolled hypertensive patients with high CV risk profile.